Perilaku Murid Sekolah Dasar Kelas III Sampai Kelas VI Tentang Mencuci Tangan Di SDN 017 Di Kelurahan Buluh Kasap Kecamatan Dumai Timur Kota Dumai Tahun 2018 - Julimar Julimar (Sistem Informasi, 2020)
Many children do not wash their hands before eating, so that the bacteria can result in hand with food will be brought in through the mouth and throat to the digestive tract so that the occurrence of an initial survey pencernaan.Based o n the survey that has been done at SD 017 Kelurahan Buluh Kasap Kota Dumai. Most students take hand washing not matching true procedures.The purpose of the research to Description Of The Behavior Of The Primary School Students In Hand washing SDN 017 Buluh Kasap Kota Dumai Tahun 2018. This is a descriptive study conducted on students in grade III and VI SD 017 Buluh Kasap Kota Dumai. The population is all elementary students in grades III through grade VI. Sampling technique with accidental sampling, with a sample of 43 people. Data collection tool used was koesioner and observation sheets . Analysis of the data used univariate data analysis. The results obtained over half (88.3%) of respondents had a high level of knowledge about hand washing, half (88.3%) of respondents have a positive attitude about hand washing, and over half (53.4%) of respondents have either no action about hand washing. In order for the implementation of hand washing behavior expected for elementary school students in order to make policy regarding hand washing, controlling, providing motivation for elementary students 19 olo desert village about handwashing, and complete facilities and infrastructure, including the provision of hand soap and paper towels or clean towel.